2010
DOI: 10.1007/s00425-010-1153-6
|View full text |Cite
|
Sign up to set email alerts
|

Calmodulin-binding transcription activator 1 mediates auxin signaling and responds to stresses in Arabidopsis

Abstract: Auxin is a key plant hormone that regulates various aspects of plant development. However, the mechanisms integrating auxin growth effects with stress responses are not fully understood. In this study, we investigated the possible role of calmodulin-binding transcription activator 1 (CAMTA1), an Arabidopsis thaliana calcium/calmodulin-binding transcription activator, in auxin signaling and its responses to different stresses. Plants harboring the AtCAMTA1 promoter fused to the GUS reporter gene revealed cell-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
90
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(92 citation statements)
references
References 62 publications
0
90
0
1
Order By: Relevance
“…efr-1 6 , ers1-10 (a weak gain-of-function mutant; ERS, ethylene receptor-related gene family member) 26 , ein4-1 (a gain-of-function mutant; EIN4, ethylene receptor-related gene family member) 27 , wei7-4 (a loss-of-function mutant; WEI7, involved in ethylene-mediated auxin increase) 28 , eicbp.b ( camta 1–3 ; SALK_108806; EICBP.B, an ethylene-induced calmodulin-binding protein) 29 , pab2/4 18 and pab2/8 18 were previously described. efr7 (SALK_205018; ERF7, a homologue of the ethylene responsive TF gene ERF1 ) and gcn2 (GABI_862B02) were from the Arabidopsis Biological Resource Center (ABRC).…”
Section: Methodsmentioning
confidence: 99%
“…efr-1 6 , ers1-10 (a weak gain-of-function mutant; ERS, ethylene receptor-related gene family member) 26 , ein4-1 (a gain-of-function mutant; EIN4, ethylene receptor-related gene family member) 27 , wei7-4 (a loss-of-function mutant; WEI7, involved in ethylene-mediated auxin increase) 28 , eicbp.b ( camta 1–3 ; SALK_108806; EICBP.B, an ethylene-induced calmodulin-binding protein) 29 , pab2/4 18 and pab2/8 18 were previously described. efr7 (SALK_205018; ERF7, a homologue of the ethylene responsive TF gene ERF1 ) and gcn2 (GABI_862B02) were from the Arabidopsis Biological Resource Center (ABRC).…”
Section: Methodsmentioning
confidence: 99%
“…The patterns of induction to multiple chemical and physical stimuli suggest the involvement of individual CAMTAs in multiple signal transduction pathways and stress responses. For example, CAMTAs have been shown to be involved in auxin signaling in growth and development as well as in stress response and may link the two pathways (Galon et al, 2010b). CAMTA1 repressor lines and camta1 mutants showed enhanced responsiveness to auxin, suggesting that in wild-type plants, enhanced expression of CAMTA1 in response to stresses suppresses the plant's responsiveness to auxin (Galon et al, 2010b).…”
Section: Impacts Of Cellular Ca 2+ Changes On Gene Expressionmentioning
confidence: 99%
“…Very recently, results showed that CAMTA1 and CAMTA2 share some functional redundancy with CAMTA3 in suppressing SA biosynthesis and the quick induction of CBF1, CBF2, and CBF3 transcription (Kim et al, 2013). AtCAMTA1 was reported to be an auxin-responsive gene, and hypocotyl elongation of AtCAMTA1 knockout or repression lines is hyperresponsive to exogenous application of auxin, indicating that CAMTA1 could regulate plant growth through the action of auxin (Galon et al, 2010a).…”
Section: The Best Characterized Cam-regulated Transcription Factors: mentioning
confidence: 99%